Complications rate of and risk factors for the unplanned reoperation of degenerative lumbar spondylolisthesis in elderly patients: a retrospective single-Centre cohort study of 33 patients - Zhong, Weiyang; Liang, Xinjie; Luo, Xiaoji; Huang, Tianji; Quan, Zhengxue (BMC geriatrics, 2020)
Background The study was to investigate the complications rate of and risk factors for unplanned reoperation among elderly patients who underwent posterior lumbar fusion (PLF) for degenerative lumbar spondylolisthesis (DLS). Methods A total of 1100 DLS patients who were older than 60 years were reviewed from January 2006 to December 2016. 33 patients underwent unplanned reoperations and were analysed and divided into two groups (group A: posterolateral fusion, 650 patients; group B: intervertebral fusion, 450 patients). Sex, body mass index (BMI), radiographic data and clinical outcome data were analysed to evaluate the complications rate of and the risk factors for unplanned reoperations. Results A total of 33 patients underwent unplanned reoperations (3%). The patients were followed up for an average of 4.20 ± 2.25 years (group A) and 4.32 ± 2.54 years (group B) without a significant difference. Significant differences were found in mean age, levels of involvement, hospital stay, surgery time, and blood loss between the groups. The causes of unplanned operation were wound infection, screw misplacement, neurological deficit, nonunion, and screw fracture, which were significant except for wound infection between the groups. Higher BMI (obesity), diabetes mellitus (DM), more bleeding and sex (female) were risk factors for complications. Cases of screw misplacement, neurological deficit, nonunion and screw fracture in group A were more significant than those in group B. Conclusion Patients with higher BMI, DM, older age, posterolateral fusion, and female sex predicted a higher incidence of unplanned reoperations. Spine surgeons may need to pay more attention to their preoperative training and to improving surgical techniques that could reduce the reoperation rate.